2012
DOI: 10.1080/03043797.2012.681863
|View full text |Cite
|
Sign up to set email alerts
|

What do final year engineering students know about sustainable development?

Abstract: This paper presents data from a project which aims to determine the level of knowledge and understanding of engineering students about Sustainable Development (SD). The data derives from a survey completed by final year engineering students in three Irish Higher Education Institutions. This paper is part of a larger study which examines the relationship between students' and teachers' understanding of SD. The results from the survey show that final year engineering students have a discipline-led conception of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 8 publications
(26 reference statements)
3
22
0
4
Order By: Relevance
“…For example, Dlouha et al's [41] study of Central European countries, including Slovenia, reported that in higher education, economic issues are not connected to environmental issues. Related studies have indicated that students lack complex understanding of sustainability issues [66] and the dominance of environmental issues among university students [64], which was supported in our study, with higher average scores on environmental-economic factors than on social factors.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…For example, Dlouha et al's [41] study of Central European countries, including Slovenia, reported that in higher education, economic issues are not connected to environmental issues. Related studies have indicated that students lack complex understanding of sustainability issues [66] and the dominance of environmental issues among university students [64], which was supported in our study, with higher average scores on environmental-economic factors than on social factors.…”
Section: Discussionsupporting
confidence: 74%
“…Nikolaou and Conlon [66] revealed the lack of students' knowledge and understanding of the complexity of sustainable development, and that they perceive a much higher importance of SD at the professional level than at a personal level. Based on the findings of our study, we argue for teaching methods supporting authentic learning that integrate personal and professional contexts and provide continuum between formal and informal learning [21].…”
Section: Discussionmentioning
confidence: 99%
“…The programmes' disciplines are civil, mechanical, structural, building services and chemical engineering. The project has already determined that final year engineering students' knowledge and understanding of SD is inadequate with significant knowledge gaps (Nicolaou and Conlon 2012). This is a result of an insufficient provision of SD competencies which is not based on a holistic approach to EESD (Nicolaou and Conlon 2013).…”
Section: Scope and Rationalementioning
confidence: 99%
“…The programmes do not provide the broad and general education for SD that engineers need in order to become agents of change for SD (Ashford 2010). Given the deficiencies in the provision for EESD that have emerged from our surveys of students (Nicolaou and Conlon 2012) and our analysis of programme content (Nicolaou and Conlon 2013) and the importance of staff to EESD, as indicated above, it was decided to explore staff's knowledge of SD and their views about its integration in engineering education. In the first instance we considered a staff survey but for reasons to do with concerns relating to possible low response rates and the limitations of survey data for exploring the underlying mechanisms shaping EESD it was decided to conduct a series of in depth interviews with programme chairs (directors) who are central figures in providing academic leadership on programmes and play a central role in programme validation and accreditation events.…”
Section: Scope and Rationalementioning
confidence: 99%
See 1 more Smart Citation